A FORMAÇÃO CONTINUADA E PRÁTICA PEDAGÓGICA: UM RETRATO DO PROGRAMA “MAIS ALFABETIZAÇÃO” EM TEIXEIRA DE FREITAS-BA - Oliveira, Paulo Vinicius Brito dos Santos (2020)
We aim to present in the present research the More Literacy Program, articulating with experience reports presented by teachers and literacy assistants during a training meeting offered by PMALFA in the city of Teixeira de Freitas - Bahia. In explaining t